APPLICATION OF COUNTER IMMUNOELECTROPHORESIS (CIE) IN THE DIAGNOSIS OF HYDATIDOSIS IN BUFFALOES - A.SANGARAN,; S.ARUNKUMAR, (International Journal of Pharma and Bio Sciences, 2013)
A study was undertaken to assess the sensitivity and specificity of Counter Immunoelectrophoresis (CIE) in the diagnosis of hydatidosis in buffaloes using sera samples collected at the time of slaughter. One hundred sera samples from buffaloes were screened for hydatidosis using fertile buffalo hydatid cyst fluid as antigen by CIE. Out of the 100 sera samples used, 61 were positive for hydatid cysts in various organs confirmed on slaughter and the remaining 39 sera were collected randomly from buffaloes without any visible hydatid cysts. Forty six samples were found positive out of the 61 samples screened by CIE with 2 samples found positive out of the 39 samples from buffaloes without any visible hydatid cysts. The sensitivity and specificity of CIE in detecting hydatidosis in buffaloes was found to be 75.41 per cent and 94.8 per cent respectively.